Are attention-deficit/hyperactivity disorder symptoms associated with negative health outcomes in individuals with psychotic experiences? Findings from a cross-sectional study in Japan - Stickley, Andrew; Shirama, Aya; Sumiyoshi, Tomiki (Frontiers in Psychiatry, 2023)
Objective: The occurrence of attention-deficit/hyperactivity disorder (ADHD) is elevated in adults with psychotic experiences (PE). However, there has been little research exploring if the presence of ADHD increases the risk for negative outcomes in individuals with PE. This study examined the association between PE and ADHD symptoms in Japanese individuals and whether the presence of ADHD symptoms increases the risk for negative health outcomes in people with PE. Method: Data were analyzed from an online sample of 1452 individuals (age 18-89; 51.5% female) collected in 2021. Information on PE was assessed with the PRIME Screen-Revised (PS-R), while the Adult ADHD Self-Report Scale (ASRS) Screener was used to measure ADHD symptoms. Information was also obtained on a number of health outcomes including anxiety and depressive symptoms and suicidal ideation. Logistic regression was used to assess associations. Results: In a fully adjusted analysis PE were associated with almost three times higher odds for ADHD symptoms (OR: 2.92, 95%CI: 1.19-7.17). In an analysis that was restricted to individuals with PE, ADHD symptoms were associated with significantly increased odds for several negative health outcomes including depressive symptoms, lifetime suicidal ideation, perceived stress and severe sleep problems. Conclusion: ADHD symptoms are comorbid in individuals with PE and increase the odds for several detrimental health outcomes in this population. Identifying co-occurring PE and ADHD/ADHD symptoms may facilitate treatment options and help prevent negative health outcomes in individuals with these comorbidities.